The diversity of the opa gene in gonococcal isolates from men who have sex with men. Issue 4 (4th August 2004) - Howie, F; Young, H; McMillan, A
Abstract : Objectives: To use a molecular typing method (opa-typing) to characterise gonococcal isolates obtained from men who have sex with men (MSM) attending a genitourinary medicine (GUM) clinic in Edinburgh during 2001. To compare the results of opa-typing with A/S (auxotype/serovar) phenotyping, and with epidemiological information obtained by contact tracing. Methods: Isolates were opa-typed by a PCR-RFLP method where the restriction fragments resulting from digestion with three separate restriction enzymes were resolved by polyacrylamide gel electrophoresis. Isolates were considered to have the same opa-type if the band patterns were identical or if they differed by one band between the three digestions. Results: 40 opa-types were detected from a collection of 73 gonococcal isolates from 61 patients. 26 opa-types were unique, being found in one individual each, 14 different opa-types were found in more than one patient. Opa-typing was found to have a discrimination index (DI) of 0.96, compared to a DI of 0.87 for A/S phenotyping, indicating that opa-typing is better at discriminating between unrelated isolates. Opa-typing confirmed three epidemiological links established by contact tracing, and uncovered a further 13 clusters of isolates. Conclusions: Opa-typing is a more discriminative method than A/S phenotyping when determining relatedness in gonococcal isolates. The ability of opa-typing to identify sexual networks not disclosed by contact tracing and conventional phenotyping make it a useful method for studying the spread of gonorrhoea with the potential to contribute to the control of this infection.